CONTEMPORARY IMPROVEMENTS IN MODERN EDUCATION OF UZBEKISTAN - Hakimjanova , Mamura (Educational Research in Universal Sciences, 2023)
This article studies the system of higher education of the Republic of Uzbekistan. The author examines the issues of reforming higher education in the context of deepening democratic reforms in a new stage of the country’s development. The paper studies topical issues of improving the activities of higher educational institutions. An attempt was made to study the current state of higher education and the most important strategic tasks facing it, which directly affect the methods, content, and also the creation of an intellectual environment for future bachelors and masters.